1985
DOI: 10.1021/bi00345a026
|View full text |Cite
|
Sign up to set email alerts
|

Histone synthesis and deposition in the G1 and S phases of hepatoma tissue culture cells

Abstract: Hepatoma tissue culture cells were synchronized in G1 and in S phase in order to examine the level of synthesis of different histone types and to determine the rate, timing, and location of their deposition onto DNA. We observe a basal level of synthesis in G1 (5% of that seen in S phase) for H2A.1, H2A.2, H3.2, H2B, and H4. The minor histone variants X and Z are synthesized at 30% of the rate observed in S cells. The rate of synthesis of the ubiquinated histones uH2A.1,2 is not as depressed in G1 cells as see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
1
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 40 publications
8
33
1
1
Order By: Relevance
“…In agreement with our global analysis (supplementary material Fig. S1C), and consistent with previous biochemical and FRAP (fluorescence recovery after photobleaching) analyses in human cells (Bönisch et al, 2012;Higashi et al, 2007;Jackson and Chalkley, 1985;Kimura et al, 2006), within the detection range of our method both variants showed a comparable extensive deposition of newly synthesized histones in euchromatin. However, the situation proved to be different at the PHC domains, where the distribution of newly synthesized histones relative to euchromatin could be categorized into one of three distinct patterns -exclusion, even distribution or enrichment (Fig.…”
Section: Different Dynamics Of H2a and H2az Deposition At Phcsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our global analysis (supplementary material Fig. S1C), and consistent with previous biochemical and FRAP (fluorescence recovery after photobleaching) analyses in human cells (Bönisch et al, 2012;Higashi et al, 2007;Jackson and Chalkley, 1985;Kimura et al, 2006), within the detection range of our method both variants showed a comparable extensive deposition of newly synthesized histones in euchromatin. However, the situation proved to be different at the PHC domains, where the distribution of newly synthesized histones relative to euchromatin could be categorized into one of three distinct patterns -exclusion, even distribution or enrichment (Fig.…”
Section: Different Dynamics Of H2a and H2az Deposition At Phcsupporting
confidence: 93%
“…In contrast to CENP-A, the deposition dynamics of H2A variants at centromeres remain unknown. Notably, H2A variants constantly exchange at a rapid rate throughout the nucleus (Bönisch et al, 2012;Higashi et al, 2007;Jackson and Chalkley, 1985;Kimura et al, 2006), raising an important question regarding their stable maintenance at a given locus. Furthermore, given that H2A.Z displays a broader localization across the genome than CENP-A, its dynamics might be distinct in different genomic compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, H2A/H2B may displace more often than H3/H4. This is consistent with the pioneering studies of Jackson and Chalkley (1985) that illustrated that the timing and location of H2A/H2B deposition into chromatin is somewhat different than H3/H4 deposition and was more evident outside of S phase. These early studies may have reflected a more frequent replacement of H2A/H2B than H3/H4 in transcribed chromatin.…”
Section: Nucleosome Displacement During Transcription Elongationsupporting
confidence: 91%
“…but not the histones H3 and H4, were actually incorporated into bulk chromatin that was separated from replicating chromatin by various fractionation means [22 -271. The incorporation occurred similarly even at the G1 stage of the cell cycle [32] or even when DNA replication was inhibited by hydroxyurea [33], though the rate of histone synthesis was also lowered under these conditions. Likewise, all five types of histone were synthesized and incorporated into chromatin in lymphocytes at the GO stage in the peripheral circulation [34].…”
Section: Resultsmentioning
confidence: 93%